Consumer Desires and the Fluctuating Balance between Liquid and Solid Consumption: The Case of Finnish Clothing Libraries - Rosenberg, Laura M; Weijo, Henri A; Kerkelä, Iina (Journal of Consumer Research, 2023)
Abstract The ongoing rise of liquid consumption manifests in the growing popularity of ephemeral, access-based, and dematerialized forms of consumption that contrast with traditional solid forms of consumption characterized by possession and strong object relationships. The literature already presents a robust understanding of what makes liquid and solid consumption appealing to consumers. What has received less attention is the co-existence of liquid and solid consumption in consumers’ lived experiences. Furthermore, the literature does not explain how the balance that consumers achieve between liquid and solid consumption fluctuates over time. This study illuminates the co-existence of liquid and solid consumption through a phenomenological inquiry of subscription-based clothing libraries, a context where solid personal possessions frequently mix with liquid accessed items in everyday use. Findings show that changes in consumer desire play a major role in consumer decisions to liquify or solidify consumption, especially over time. Overall, the study provides new theoretical insights into liquid and solid consumption, consumer desire, and burdens of access-based consumption.